Separate Consent for Anesthetic Practice: Need of the Moment - Shrestha, Anil; Shrestha, Gentle S; Pradhan, Saurabh; Joshi, Pankaj (Journal of Institute of Medicine Nepal, 2020)
Decades of refinement and modifications have led the modern anaesthetic practice to be conducted so smoothly and safely, that sometimes we take for granted the enormous amount of risks involved with it. Furthermore, with the evolution of monitoring techniques, and discovery of safer drugs, anesthesia has facilitated the conduction of complex surgeries on sicker patients, and older patients. The expansion to critical care and pain management services has added another dimension to this field, with anesthesiologists not just working as facilitators for another procedure, but acting as primary physicians. Anesthesiologists are among the few clinicians, who are involved in patient morbidity and mortality in their daily routine. With the ever-changing ethical and legal background, the significance of obtaining a separate consent for anesthesia needs to be timely evaluated. In this review, we have discussed the significance of a separate consent for anesthesia and highlight its various aspects.